Evaluation arrhythmias in athlete horses with poor performance (Research, Society and Development, 2020)
The aim of this study was to correlate the importance of arrhythmias in English horses with poor performance. Sixteen horses (10 males and 6 females) were evaluated, aged between 2 and 6 years and weighing 474.5 ± 39.4 kg. These were selected according to the occurrence or not of low performance, in groups: low performance group (BD) and control group (CTL). A continuous electrocardiographic exam (Holter) was performed, being evaluated at rest and during exercise, standardized for all. Arrhythmias were observed in both groups, classified as second-degree atrioventricular block (BAV2), sinus block (BS), premature pre-ventricular complex (CPVP), premature ventricular complex (CVP) and ventricular tachycardia (VT). BAV2 was the most frequent arrhythmia with an average of 1.91 BAV2/h in the BD group and 3.8 BAV2/h in the CTL group. As for the occurrence of BS, the average was 0.76 BS/h in the BD group and 0.72 BS/h in the CTL group. Premature pre-ventricular complex averaged 0.12 CPVP/h in the CTL group and 0.21 CPVP/h in the BD group. The comparison of the occurrence of BAV2, BS, CPVP and DVP in both groups, did not obtain statistically significant differences. The results suggest that there was no influence of these arrhythmias on the low performance of the animals evaluated.